2018
DOI: 10.3390/molecules23092222
|View full text |Cite
|
Sign up to set email alerts
|

Native V. californicum Alkaloid Combinations Induce Differential Inhibition of Sonic Hedgehog Signaling

Abstract: Veratrum californicum is a rich source of steroidal alkaloids such as cyclopamine, a known inhibitor of the Hedgehog (Hh) signaling pathway. Here we provide a detailed analysis of the alkaloid composition of V. californicum by plant part through quantitative analysis of cyclopamine, veratramine, muldamine and isorubijervine in the leaf, stem and root/rhizome of the plant. To determine whether additional alkaloids in the extracts contribute to Hh signaling inhibition, the concentrations of these four alkaloids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…2020 identified that saquinavir, lithospermic acid, and 11m_32045235 were promising therapeutic compound against SARS-Cov-2 main protease, whereas Selvaraj et al 2020 demonstrated that TCM 57,025, TCM 3495, TCM 5376, TCM 20,111, and TCM 31,007 were therapeutic compounds that interact with the substrate-binding site of N7-MTase [ 194 , 195 ]. On the same trend, Cruz et al 2018 concluded that ZINC91881108 was potent compound against RIPK2, whereas Simoben et al 2018 demonstrated eight novel N-(2,5-dioxopyrrolidin-3-yl)-n-alkylhydroxamate derivatives as smHDAC8 inhibitors with IC 50 values ranging from 4.4 to 20.3 µM against smHDAC8 [ 196 , 197 ] [Fig. 4 ].…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…2020 identified that saquinavir, lithospermic acid, and 11m_32045235 were promising therapeutic compound against SARS-Cov-2 main protease, whereas Selvaraj et al 2020 demonstrated that TCM 57,025, TCM 3495, TCM 5376, TCM 20,111, and TCM 31,007 were therapeutic compounds that interact with the substrate-binding site of N7-MTase [ 194 , 195 ]. On the same trend, Cruz et al 2018 concluded that ZINC91881108 was potent compound against RIPK2, whereas Simoben et al 2018 demonstrated eight novel N-(2,5-dioxopyrrolidin-3-yl)-n-alkylhydroxamate derivatives as smHDAC8 inhibitors with IC 50 values ranging from 4.4 to 20.3 µM against smHDAC8 [ 196 , 197 ] [Fig. 4 ].…”
Section: Applications Of Artificial Intelligence In Drug Development mentioning
confidence: 99%
“…Initially given the name alkaloid Q, 4 is produced by V. californicum and is known to be a Hh signaling pathway antagonist as well as a non-depolarizing action potential blocker in the giant axon of squid and crayfish [ 1 , 73 , 80 ]. Compound 4 is not teratogenic in sheep, but did demonstrate marginal activity as a teratogen in hamsters [ 81 ].…”
Section: Alkaloids Identified In Veratrum Californicummentioning
confidence: 99%
“…Compound 4 is not teratogenic in sheep, but did demonstrate marginal activity as a teratogen in hamsters [ 81 ]. The bioactivity of 4 was tested in combination with 2 and 3 by measuring Gli protein activity in Shh-Light II cells [ 73 ]. The Gli family members are transcription factors that can be monitored in order to determine whether the Hh pathway is activated or not [ 84 , 85 ].…”
Section: Alkaloids Identified In Veratrum Californicummentioning
confidence: 99%
See 2 more Smart Citations